91.3k views
1 vote
Subtract: (2x^2-7x+5)-(-6x^2-4x-2)

A. -4x^2-11x+3
B. -4x^2-5x+3
C. 8x^2-13x+7
D. 8x^2-3x+7

User KaronatoR
by
5.3k points

2 Answers

2 votes

Answer:

8x^2-3x+7

Explanation:

By simplifying the expression.

User Ajay Thakur
by
5.6k points
5 votes

Answer:


\large\boxed{D.\ 8x^2-3x+7}

Explanation:


(2x^2-7x+5)-(-6x^2-4x-2)\\\\=2x^2-7x+5-(-6x^2)-(-4x)-(-2)\\\\=2x^2-7x+5+6x^2+4x+2\qquad\text{combine like terms}\\\\=(2x^2+6x^2)+(-7x+4x)+(5+2)\\\\=8x^2-3x+7

User ConnectionLost
by
5.3k points